Regulatory T Cells in Radiotherapeutic Responses - Schaue, Dörthe; Xie, Michael W.; Ratikan, Josephine A.; McBride, William H. (Frontiers in Oncology, 2012)
Radiation therapy (RT) can extend its influence in cancer therapy beyond what can be attributed to in-field cytotoxicity by modulating the immune system. While complex, these systemic effects can help tip the therapeutic balance in favor of treatment success or failure. Engagement of the immune system is generally through recognition of damage-associated molecules expressed or released as a result of tumor and normal tissue radiation damage. This system has evolved to discriminate pathological from physiological forms of cell death by signaling “danger”. The multiple mechanisms that can be evoked include a shift towards a pro-inflammatory, pro-oxidant microenvironment that can promote maturation of dendritic cells and, in cancer treatment, the development of effector T cell responses to tumor-associated antigens. Control over these processes is exerted by regulatory T cells (Tregs), suppressor macrophages and immunosuppressive cytokines that act in consort to maintain tolerance to self, limit tissue damage, and re-establish tissue homeostasis. Unfortunately, by the time RT for cancer is initiated the tumor-host relationship has already been sculpted in favor of tumor growth and against immune-mediated mechanisms for tumor regression. Reversing this situation is a major challenge. However, recent data show that removal of Tregs can tip the balance in favor of the generation of radiation-induced anti-tumor immunity. The clinical challenge is to do so without excessive depletion that might precipitate serious autoimmune reactions and increase the likelihood of normal tissue complications. The selective modulation of Treg biology to maintain immune tolerance and control of normal tissue damage, while releasing the “brakes” on anti-tumor immune responses, is a worthy aim with promise for enhancing the therapeutic benefit of RT for cancer.